1998
DOI: 10.1038/sj.bjp.0701884
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide‐induced cytotoxicity attenuation by thiopentone sodium but not pentobarbitone sodium in primary brain cultures

Abstract: 1. We describe the effects of barbiturates on the neurotoxicity induced by nitric oxide (NO) on foetal rat cultured cortical and hippocampal neurones. Cessation of cerebral blood flow leads to an initiation of a neurotoxic cascade including NO and peroxynitrite. Barbiturates are often used to protect neurones against cerebrovascular disorders clinically. However, its neuroprotective mechanism remains unclear. 2. In the present experiment, we established a new in vitro model of brain injury mediated by NO with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 48 publications
2
34
0
Order By: Relevance
“…[25][26][27] During cerebral ischemia, neuronal nitric oxide synthase is activated 25 which can result in cytotoxicity by mechanisms which include free radical damage, inactivation of enzymes involved in mitochondrial respiration, and energy depletion subsequent to activation of poly-ADP ribose synthase. 28 In a neuronal cell culture model of nitric oxide induced cytotoxicity, Shibuta et al 29 assessed the effect of thiopentone and pentobarbitone on cell death. They observed that cell death was reduced by thiopentone but not pentobarbitone.…”
Section: Nitric Oxide Neurotoxicitymentioning
confidence: 99%
“…[25][26][27] During cerebral ischemia, neuronal nitric oxide synthase is activated 25 which can result in cytotoxicity by mechanisms which include free radical damage, inactivation of enzymes involved in mitochondrial respiration, and energy depletion subsequent to activation of poly-ADP ribose synthase. 28 In a neuronal cell culture model of nitric oxide induced cytotoxicity, Shibuta et al 29 assessed the effect of thiopentone and pentobarbitone on cell death. They observed that cell death was reduced by thiopentone but not pentobarbitone.…”
Section: Nitric Oxide Neurotoxicitymentioning
confidence: 99%
“…It may not be surprising that propofol and thiopental improved recovery from PQ acute toxicity in the cell culture study, because they are known to be free radical scavengers in vitro [13,14,15]. As thiopental was less potent than propofol in scavenging O 2 -, a larger concentration of thiopental was required to improve cell viability in the present study.…”
Section: Discussionmentioning
confidence: 75%
“…Ventilatory support is usually necessary for the treatment of PQ poisoning because of the consequences of the severe lung injury. Of the hypnotics and sedatives used in the management of mechanical ventilation, propofol and thiopental are recognized as having a free radical scavenging activity [13,14,15]. Because of this property, propofol is proposed to be useful for patients in intensive care units with multiorgan failure or acute respiratory distress syndrome [16].…”
mentioning
confidence: 99%
“…Decompressive craniectomy has also been shown to decrease ICP as well as improve morbidity and mortality in TBI patients [1,10]. In the adult and pediatric populations, barbiturate coma and craniectomy are currently being used as a second tier means for controlling intracranial hypertension [4,7,10,11,12]. However, the combination of barbiturate coma and craniectomy for pediatric TBI, specifically in the severely injured population (GCS <5), has been limited to few studies.…”
Section: Introductionmentioning
confidence: 99%